Nuclear Magnetic Resonance in Costa Rica: a historical perspective - Borloz-Chinchilla, Jose Andrés (2024)
Nuclear Magnetic Resonance (NMR) is a widely used technique for the elucidation and structural characterization of organic molecules thanks to the interaction of matter with a magnetic field. Since the acquisition of the first NMR in Costa Rica, at the end of the 70s, Costa Rican science in general, and chemistry in particular, have taken a significant step, by generating impact research and many publications and theses. For the first time in the history of Costa Rican science, a detailed study of the development of NMR in the country is presented, thanks to an exhaustive review of primary and secondary sources. This document shows a historical compilation of the NMR equipment presented in the country, the results obtained with them and a historical perspective about its use.